Mouse Model of Cytomegalovirus Disease and Immunotherapy in the Immunocompromised Host: Predictions for Medical Translation that Survived the “Test of Time” - Matthias J. Reddehase; Niels A. W. Lemmermann (Viruses, 2018)
Human Cytomegalovirus (hCMV), which is the prototype member of the β-subfamily of the herpesvirus family, is a pathogen of high clinical relevance in recipients of hematopoietic cell transplantation (HCT). hCMV causes multiple-organ disease and interstitial pneumonia in particular upon infection during the immunocompromised period before hematopoietic reconstitution restores antiviral immunity. Clinical investigation of pathomechanisms and of strategies for an immune intervention aimed at restoring antiviral immunity earlier than by hematopoietic reconstitution are limited in patients to observational studies mainly because of ethical issues including the imperative medical indication for chemotherapy with antivirals. Aimed experimental studies into mechanisms, thus, require animal models that match the human disease as close as possible. Any model for hCMV disease is, however, constrained by the strict host-species specificity of CMVs that prevents the study of hCMV in any animal model including non-human primates. During eons of co-speciation, CMVs each have evolved a set of “private genes„ in adaptation to their specific mammalian host including genes that have no homolog in the CMV virus species of any other host species. With a focus on the mouse model of CD8 T cell-based immunotherapy of CMV disease after experimental HCT and infection with murine CMV (mCMV), we review data in support of the phenomenon of “biological convergence„ in virus-host adaptation. This includes shared fundamental principles of immune control and immune evasion, which allows us to at least make reasoned predictions from the animal model as an experimental “proof of concept.„ The aim of a model primarily is to define questions to be addressed by clinical investigation for verification, falsification, or modification and the results can then give feedback to refine the experimental model for research from “bedside to bench„.